El cambio de líquido a gaseoso de los organismos interagenciales del derecho internacional público en América Latina: una mirada desde la teoría de juegos (Tema Central) - Quinatoa Paucar, Frank (2022)
At the beginning of the 21st century, Latin American integration in organizations such as UNASUR, MERCOSUR and CELAC was projected as a promising future for multilateral cooperation. However, the internal political processes of each nation shelved the development of ambitious projects in multilateralism. This essay proposes an analysis, using the theory of games, on the political, economic, and social factors that shape multilateralism in Latin America. Through a constructivist approach, the paper argues that the states that integrate the intergovernmental organizations of public international law are agencies. This allows to understand that the multilateral agencies in Latin America undergo periodic changes regarding the institutionalization of their agencies. It is explained from the change of states of matter: while the liquid adapts and permeates as ideas in the discursive atmosphere, when there is a breaking point, this changes state and turns to gaseous, dispersing both the states parties and the ideas that founded the international body. It is concluded that, since 2020, the global and regional challenges faced by states in terms of security, environment and trade require a rethinking of the foundations of multilateralism and current Public International Law in Latin America.